2020
DOI: 10.3748/wjg.v26.i31.4607
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a pattern recognition metabolomics model for the diagnosis of hepatocellular carcinoma

Abstract: BACKGROUND Early diagnosis of hepatocellular carcinoma may help to ensure that patients have a chance for long-term survival; however, currently available biomarkers lack sensitivity and specificity. AIM To characterize the serum metabolome of hepatocellular carcinoma in order to develop a new metabolomics diagnostic model and identifying novel biomarkers for screening hepatocellular carcinoma based on the pattern recognition method. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This result was consistent with a previous study in serum samples of HBV cirrhosis and HCC. 31 The previous studies had indicated that arginine had a promising function in the liver via mediating the nitric oxide signaling pathway, which maintained vascular health conditions and impacted hepatic circulation. 32 Besides, it also works on the urea cycle to facilitate fatty acid oxidation and ammonia detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with a previous study in serum samples of HBV cirrhosis and HCC. 31 The previous studies had indicated that arginine had a promising function in the liver via mediating the nitric oxide signaling pathway, which maintained vascular health conditions and impacted hepatic circulation. 32 Besides, it also works on the urea cycle to facilitate fatty acid oxidation and ammonia detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported changes in glutamine and glutamate levels in the blood and urine of cancer patients, and suggested that these two metabolites could be used as potential metabolic markers to effectively distinguish cancer patients from non-cancerous individuals. Seven studies found higher levels of glutamine ( 21 , 22 , 27 31 ) and three studies observed lower glutamine levels in patients with cancer ( 32 , 35 , 36 ). These findings may be attributed to enhanced glutamine catabolism, which produces more glutamate.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosismentioning
confidence: 99%
“…However, due to the similarity existed between the metabolic features between HCC and liver cirrhosis, a pattern recognition approach has been developed and employed for HCC metabolomics study based on sequential feature selection in combination with linear discriminant analysis ( 77 ). When combined with AFP diagnostic model, this recognition analysis is effective enough to distinguish HCC from healthy controls or liver cirrhosis than conventional data processing methods ( 78 ). Additionally, a LC-MS-based metabolomics study have established a network-based feature selection method (NFSM) to define metabolites with the most discriminant capacity of outcome prediction.…”
Section: Metabolomics Approaches For Metabolite Profilingmentioning
confidence: 99%